Multidimensionality in the Integration of First- and Second-Generation Migrants in Europe: A Conceptual and Empirical Investigation. Issue 1 (March 2023) - Fajth, Veronika; Lessard-Phillips, Laurence
Immigrant integration scholarship increasingly discusses integration as a multidimensional process. Yet there is considerable inconsistency in how that multidimensionality is conceptualized. This article posits that there are two different logical approaches by which multidimensional frameworks of integration tend to outline their dimensions: the "thematic" (or conceptually driven) approach and the "empirical" approach. We contend that these two approaches lead to differently structured multidimensional frameworks of immigrant integration. To demonstrate these points, we, first, review different conceptualizations and approaches to multidimensionality in prior immigrant integration research, focusing largely on Europe. Through a synthesis of these prior approaches, we outline eight thematic dimensions of integration prevalent in the existing literature. Second, we conduct an original study with cross-European data on first- and second-generation migrants (ESS7 2014-15, N = 1, 066) to outline a multidimensional framework based on empirical patterns of co-variation (or distinction) among integration-related outcomes. Our factor analysis of 18 common indicators of integration reveals five main dimensions of integration, with some items relating strongly to more than one dimension. These five "empirical" dimensions (economic/structural integration; health; subjective well-being; cultural assimilation and civic/political integration; and minority socialization) differ from the eight typical "thematic" dimensions identified in existing scholarship in key respects, which we discuss alongside potential connections between integration aspects as suggested by our findings (e.g., between economic and civic/political or between civic/political and cultural aspects). Overall, our article advances migration studies by helping us think more critically about the multidimensionality of immigrant integration and contributes to an emerging literature on integration's multidimensionality.